Rembrandt's naked truth drawing nude models in the golden age - Noorman, Judith; De Witt, David A. 1967-; Rembrandt Harmensz van Rijn 1606-1669 (The Rembrandt House Museum, 2016)
Rembrandt and his pupils drew from the nude model in the 17th century. They took part in a new trend of drawing from models, but with different approach from their contemporaries. Rembrandt'sdrawings were especially realistic and he was criticized for presenting reality instead of pursuing the ideals of beauty then current.
This catalogue accompanies the exhibition "Rembrandt's naked truth. Drawing nude models in the Golden Age" at the Rembrandt House Museum, 12 February-16 May 2016
Keywords: Rembrandt -- Harmensz van Rijn -- 1606-1669; Aktdarstellung; Zeichnung; Ausstellungskatalog -- Rembrandthuis -- 12.02.2016-16.05.2016 -- Amsterdam; Bildband